Efficacy and safety of ascending methotrexate dose in combination with adalimumab: the randomised CONCERTO trial. Issue 6 (18th February 2014) - Burmester, Gerd-Rűdiger; Kivitz, Alan J; Kupper, Hartmut; Arulmani, Udayasankar; Florentinus, Stefan; Goss, Sandra L; Rathmann, Suchitrita S; Fleischmann, Roy M
Abstract : Objective: CONCERTO was a randomised, double-blind, parallel-armed study of methotrexate (MTX) in combination with adalimumab to assess whether an increasing trend of efficacy and decreased safety exists when increasing MTX dose in patients with early rheumatoid arthritis (RA). Methods: Early, biologic and MTX-naive RA patients (N=395) were evenly randomised to open-label adalimumab (40 mg every other week) plus weekly blinded 2.5, 5, 10 or 20 mg MTX for 26 weeks. Clinical, radiographic and functional outcomes were analysed using two-sided linear trend tests or one-way analysis of covariance. Results: Statistically significant increasing trends were observed in the proportion of patients achieving the primary endpoint, 28-joint count disease activity score with C reactive protein (DAS28(CRP)) <3.2 (42.9%, 44.0%, 56.6% and 60.2% for 2.5, 5, 10 or 20 mg/week MTX, respectively), DAS28(CRP) <2.6 and American College of Rheumatology 50/70/90 responses with increasing doses of MTX in combination with adalimumab. No statistical differences in minimal clinically important differences in physical function were detected. Statistically significant trends for achieving low disease activity and remission were demonstrated with increasing MTX dose by validated clinical indices; differences comparing 10 and 20 mg MTX were minimal. Adalimumab serum concentrations increased with ascending dose up to 10 mg MTX. More patients experienced infectious adverse events with increasing MTX dose. Conclusions: Increasing doses of MTX in combination with adalimumab demonstrated a statistically significant trend in improved clinical outcomes that mimicked the adalimumab pharmacokinetic profile. In early RA patients initiating adalimumab combination therapy, efficacy of 10 and 20 mg/week MTX appeared equivalent.